Developing Learning about the Value of Unity in Ethnic, Religious, Racial, and Inter-Group Diversity through Project-Based Learning Models with Lapbooks - Fadhilah Aini; Karim Suryadi; Asep Mahpudz; Kokom Komalasari; Nurul Husna (Universitas Muhammadiyah Mataram, 2026)
Indonesia has a rich diversity of ethnicity, religion, race, and intergroup (SARA) with more than 1,300 ethnic groups and six official religions, yet the challenge of intolerance in schools still occurs frequently. This study developed a lapbook-based Project Based Learning (PjBL) model to instill the value of unity in ethnicity, religion, race, and intergroup (SARA) diversity in PPKn learning for seventh-grade students at Baitul Quran Darut Tauhid School, Bandung, to address the challenge of intolerance that is still rampant among adolescents. The main objective is to design a systematic learning plan with core components that transform passive learning into authentic projects, thereby enhancing cognitive understanding, tolerance attitudes, and cross-group collaboration in accordance with the Pancasila Student Profile and the Independent Curriculum. This research method is descriptive qualitative with 9 seventh-grade students as participants through purposeful sampling, data collection through participant observation during six PjBL phases, semi-structured interviews, and content analysis of 12 interactive lapbooks produced, analyzed through thematic data reduction, matrix presentation, and source triangulation for validity. The results of the study indicate that effective learning planning produces a visualization lapbook of SARA harmony (ethnic flap, racial-intergroup graph), increasing tolerance attitudes, intergroup collaboration, with integrated authentic assessments that coordinate holistic transformation in 21st-century 4C skills. The implications of the study produce a ready-to-use lapbook-based PjBL module for multicultural schools, which reduces SARA polarization and strengthens national cohesion through the best practices of the Merdeka Curriculum.